Treatment of an accident of imidacloprid poisoning - Zeng, Mei; Shi, Mengdi; Jian, Xiangdong; Dong, Laidong (Frontiers in Pharmacology, 2024)
Objective: Accidental oral imidacloprid poisoning occurred in a family in Shandong, China, in May 2023. This study aimed to analyze the clinical characteristics of this imidacloprid poisoning event and investigated the detection of toxicants. Methods: Clinical data of four patients with oral imidacloprid poisoning were collected and retrospectively analyzed. The relevant literature was then reviewed. Results: Four patients from the same family received different oral doses of imidacloprid. The main clinical manifestations were digestive and neurological symptoms, including nausea, vomiting, and varying degrees of consciousness. Laboratory tests showed an increased white blood cell count, neutrophil proportion, and mild elevation of transaminase and urea nitrogen levels in some patients. Following comprehensive treatment, which included hemoperfusion, gastric lavage, total gastrointestinal decontamination, and drug symptomatic treatment, the patient's symptoms were quickly relieved, and the concentration of imidacloprid in the blood rapidly decreased. Conclusion: Toxicant detection is an important criterion for the differential diagnosis of poisoning and is helpful for disease assessment, treatment plan formulation, and in determining patient prognosis. Comprehensive treatment is an effective therapy for oral imidacloprid poisoning.